2011
DOI: 10.1177/000348941112001107
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Packing with Strips of Cured Pork as Treatment for Uncontrollable Epistaxis in a Patient with Glanzmann Thrombasthenia

Abstract: To our knowledge, this represents the first description of nasal packing with strips of cured pork for treatment of life-threatening hemorrhage in a patient with Glanzmann thrombasthenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Overall, 49 patients were identified in case reports and were treated with rFVIIa for 36 bleeding episodes and 29 surgical procedures . Patients ranged in age from 1 to 60 years; 53% were female and 47% were male (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 49 patients were identified in case reports and were treated with rFVIIa for 36 bleeding episodes and 29 surgical procedures . Patients ranged in age from 1 to 60 years; 53% were female and 47% were male (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In all, 40 case reports were identified that included 49 patients in whom rFVIIa was used as part of their treatment regimen; in six case reports, the same patient was treated for bleeding episodes and surgical procedures. Twenty‐four case reports described 29 patients treated for 36 bleeding episodes, and 22 case reports described 27 patients treated for 29 invasive, surgical or dental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…This real‐time case study has informed my decision to pass on the funding announcement that arrived in my inbox today. After all, many landmark papers have been published without NIH funding …”
Section: Discussionmentioning
confidence: 99%
“…5 The intervention stopped bleeding "promptly, effectively, and without sequelae" on two occasions. Nasal bleeding stopped within 24 hours, and the patient was discharged within 72 hours.…”
mentioning
confidence: 97%